Effect of chemicals surface treatment of PVD TiN coated WC on the coating adhesion - Mohd Zukee, Khairul Izani (2014)
Substrate surface treatment prior to the coating deposition is very important in order to obtain good coating adhesion. There are various substrate treatment methods such as polishing, grinding, water peening, and chemical treatment carried out in order to modify the surface characteristics of the substrate. There are quite abundant of research have been done by previous researchers on the substrate surface treatments and one of the methods used was chemical treatment using alkaline and acid solution which was typically performed on tungsten carbide (WC) prior to the deposition of diamond coatings by chemical vapour deposition (CVD). However, study on the effect of substrate chemical treatment using alkaline and acid solution on WC prior to the PVD TiN coating deposition on the coating adhesion is lacking. Adhesion between deposited coatings and substrate is one of the most important success criteria of coating process. The aim of this research is to determine the effect of substrate chemical treatment method using ultrasonic cleaner on the adhesion of TiN PVD coated tungsten carbide. The input parameters evaluated were types of solutions and treatment time. While, the output responses evaluated were surface energy, cobalt content, surface roughness, and adhesion. The characterizations were carried out using sessile drop, SEM/EDX, AFM and Rockwell indenter. The experimental approach adopted was general factorial design. Minitab version 16 software was utilized to analyze the collected data. The chemical treatment using acid for 20 minutes was found to improve the coating adhesion due to formation of uniform peaks and valleys surface morphology. It was found that the coating adhesion was dependent on both surface morphology and surface roughness of the substrate. The cobalt content on the surface layer seems to affect the coating adhesion as well. It was concluded that the substrate surface characteristics were closely related to the performance of the TiN coated inserts.